SCHEDULING OF PAINTED PRODUCTS AT PT. ABC WITH A BRANCH, BOUND, AND NEIGHBORHOOD SEARCH ALGORITHM TO MINIMIZE THE MEAN FLOW TIME - Ary Kurniati; Ahmad Fatoni; Iqbal Fahmi (Journal of Industrial Engineering & Management Research, 2022)
- PT. ABC was a manufactur company which on the job of metal coating (ZINCALUME) and painted coating (COLORBOND). Its product manufacturing was carrried in metal coating MCL 2 (Metal Coating Line 2) plant, paint coating or painting product was the most demanded by costumer expecially in MCL 2. So that, it was needed a processing time quickly, For it solution, appropriately with a scheduling. The background of this research was a PT. ABC has not been able to fill all of customer orders, because MCL 2 machine was be still new, and has not been sequenced that caused bottleneck. Method of this research was a branch and bound and neighborhood search algorthm. The purpose of this research was to minimize mean flow time at MCL 2. Existing scheduling which used by the company was a FCFS (First Come First Served). New scheduling would be divided the products into two batch which based on dimensions that were, 0,20 x 914 mm and 0,25 x 914 mm. In existing conditon, mean flow time on dimensions of 0,20 x 914 mm and 0,25 x 914 mm were 43,23 hours and 182,76 hours. The research’s result of mean flow time proved that the new scheduling by using branch and bound and neighborhood search algorthm on batch of 0,20 x 914mm was 18,42 hours, with its sequencing was a job 14- job 21- job 20- job 11- job 15 – job 8- job 3 –job 4- job 9- job 7, and then, with a neighborhood search, its sequencing was a job 14- job 20- job 21- job 11- job 15 – job 8- job 3 –job 4- job 9- job 7. For the bacth of 0,25 x 914mm , on branch and bound algorthm, it sequencing was a job 6- job 18- job 2- job 22- job 5- job 10- job 19- job 16- job 12- job 1- job 23- job 17- job 13, and then with neighborhood search , its sequencing was a job 6- job 18- job 2- job 22- job 5- job 10- job 19- job 12- job 16- job 1- job 17- job 23- job 13, they had 147,13 hours for mean flow time. Lowering of mean flow time between existing conditon with two method which used, on batch of 0,20 x 914 mm was a 57 percent and then for 0,25 x 914 mm, was a 19 percent.